Evaluating urban land-use demarcation and implementation for various urban functions using GIS and survey-based data: The case of Abuja City, Nigeria - Enoguanbhor, Evidence; Chukwurah, Gladys; Enoguanbhor, Eveline; John-Nsa, Chioma; Isimah, Matthew; Edo, Iwebuke; Achenui, Robert; Matemilola, Saheed; Fotang, Chefor; Ijioma, Uche; Ibrahim, Esther (Town and Regional Planning, 2023)
Urban planning implementation is a crucial process of urban planning to improve, attain, and maintain urban sustainability globally. However, the implementation process for land use demarcated for various urban functions is being confronted by various challenges in the Global South. This study aims to integrate questionnaire surveys of urban and regional planning experts and Geographic Information Systems (GIS), in order to investigate the level of urban planning implementation of land use demarcated for various urban functions to support strategic actions for urban sustainability. Using Abuja, Nigeria, as a case study, an urban plan, urban impervious surface map, and questionnaire data were collected, and an integrated method analysis, including qualitative and quantitative (descriptive, Euclidean Distance Modelling, and Linear Regression Modelling) was deployed. Key findings show that the vast majority of experts in urban and regional planning perceive the implementation of all land use for various urban functions to be between moderate and very high levels, except that of industrial land use perceived to be between moderate and low levels. GIS findings show that, while land uses demarcated for transportation, commercial, educational, and institutional functions are positively and significantly associated with the urban impervious surface, industrial land use and urban green spaces are negatively associated. Findings show that abuse of official privileges by distorting master plans, political interference, compromise by public servants, and inadequate funding are key challenges for urban planning implementation on land use demarcated for various urban functions. The findings in this study are crucial for strategic decision makers in urban planning to improve the implementation process for various urban land-use functions and urban sustainability in the Global South, in general, and in sub-Saharan Africa, in particular.